"A Vegetarian vs. Conventional Hypocaloric Diet: The Effect on Physical Fitness in Response to Aerobic Exercise in Patients with Type 2 Diabetes." A Parallel Randomized Study - Veleba, Jiri; Matoulek, Martin; Hill, Martin; Pelikanova, Terezie; Kahleova, Hana (Nutrients, 2016)
It has been shown that it is possible to modify macronutrient oxidation, physical fitness and resting energy expenditure (REE) by changes in diet composition. Furthermore, mitochondrial oxidation can be significantly increased by a diet with a low glycemic index. The purpose of our trial was to compare the effects of a vegetarian (V) and conventional diet (C) with the same caloric restriction (-500 kcal/day) on physical fitness and REE after 12 weeks of diet plus aerobic exercise in 74 patients with type 2 diabetes (T2D). An open, parallel, randomized study design was used. All meals were provided for the whole study duration. An individualized exercise program was prescribed to the participants and was conducted under supervision. Physical fitness was measured by spiroergometry and indirect calorimetry was performed at the start and after 12 weeks Repeated-measures ANOVA (Analysis of variance) models with between-subject (group) and within-subject (time) factors and interactions were used for evaluation of the relationships between continuous variables and factors. Maximal oxygen consumption (VO2max) increased by 12% in vegetarian group (V) (F = 13.1, p < 0.001, partial η² = 0.171), whereas no significant change was observed in C (F = 0.7, p = 0.667; group × time F = 9.3, p = 0.004, partial η² = 0.209). Maximal performance (Watt max) increased by 21% in V (F = 8.3, p < 0.001, partial η² = 0.192), whereas it did not change in C (F = 1.0, p = 0.334; group × time F = 4.2, p = 0.048, partial η² = 0.116). Our results indicate that V leads more effectively to improvement in physical fitness than C after aerobic exercise program.
Keywords: sportovní výkon; kombinovaná terapie; Diet, Vegetarian; Humans; redukční dieta; lidé středního věku; Overweight; Insulin Resistance; Diet, Reducing; Oxygen Consumption; Female; tělesná výkonnost; type 2 diabetes; Administration, Oral; lidé; physical fitness; Basal Metabolism; hyperglykemie; dieta vegetariánská; hypoglykemie; Diabetes Mellitus, Type 2; Hypoglycemic Agents; Hyperglycemia; Hypoglycemia; Energy Metabolism; ženské pohlaví; energetický metabolismus; Male; Middle Aged; inzulinová rezistence; diabetická dieta; Czech Republic; spotřeba kyslíku; Diet, Diabetic; maximal performance; hypoglykemika; Athletic Performance; Exercise; aplikace orální; maximal oxygen consumption; Combined Modality Therapy; Česká republika; mužské pohlaví; vegetarian diet; cvičení; diabetes mellitus 2. typu; bazální metabolismus; Physical Fitness; insulin sensitivity; nadváha